Millimeter-wave hetero-integrated sources in InP-on-BiCMOS technology. Issue 3 (12th May 2014) - Berroth, Manfred; Jacob, Arne F.; Schmidt, Lorenz-Peter; Jensen, Thomas; Al-Sawaf, Thualfiqar; Lisker, Marco; Glisic, Srdjan; Elkhouly, Mohamed; Kraemer, Tomas; Ostermay, Ina; Meliani, Chafik; Tillack, Bernd; et al.
<x content-type="archive" xml:space="preserve">Abstract</x> The paper presents millimeter-wave (mm-wave) signal sources using a hetero-integrated InP-on-BiCMOS semiconductor technology. Mm-wave signal sources feature fundamental frequency voltage-controlled oscillators (VCOs) in BiCMOS, which drive frequency multiplier–amplifier chains in transferred-substrate (TS) InP-DHBT technology, heterogeneously integrated on top of the BiCMOS wafer in a wafer-level bonding process. Both circuits are biased through a single set of bias pads and compact low-loss transitions from BiCMOS to InP circuits and vice versa have been developed, which allows seamless signal routing through both technologies exhibiting 0.5 dB insertion loss up to 200 GHz. One VCO operates at 82 GHz with a tuning range of 600 MHz and an output power of approximately 8 dBm. A frequency doubler combined with this VCO circuit delivers 0 dBm at 164 GHz and a frequency tripler with a similar VCO delivers −10 dBm at 246 GHz. Another hetero-integrated W-band doubler–amplifier circuit demonstrates 12.9 dBm saturated output power with 5.9 dB conversion gain at 96 GHz. A direct comparison of the TS InP-DHBT MMIC with either silicon or traditional AlN carrier substrates shows the favorable properties of the hetero-integrated process discussed here. The results demonstrate the feasibility of hetero-integrated circuits operating well above 100 GHz.